Influence of the crystal plane orientation in enhancing the electrochemical performance of a trication-substituted cathode for Li-ion batteries - Shivamurthy, Bogalera Papaiah; Thripuranthaka, Marulasiddappa; Shelke, Manjusha V.; Nayaka, Girish Praveen (Energy and Fuels, 2024)
High-voltage spinel cathodes with low nickel are promising candidates for Li-ion batteries owing to their high energy and power density, thermal stability, and eco-friendliness. However, the high operating voltage (similar to 4.7 V) leads to the decomposition of electrolytes, structural disorder, and deterioration of the cathode-electrolyte interphase (CEI) as well as hinders practical capability. We have synthesized trication-substituted spinel cathode materials with exposed (111) crystal planes and truncated octahedral shapes. These materials have demonstrated high specific discharge capacity and high rate capability up to 1000 cycles with a voltage window of 3.5-5 V. The crystal plane orientation of these materials has been investigated using X-ray diffraction of electrodes and electron microscopic studies and correlated with the electrochemical performance of the surface plane of exposed cathode materials. Among the three synthesized materials, the LMNFA2 cathode has shown a specific discharge capacity of 109.29 mAh g(-1) at 1 C after 1000 cycles with a capacity retention of 76.3%, which is nearly equal to the previously reported dual-phase material with the same metal compositions.